Negotiations in co-production and development of digital courses in higher education: Experiences from an observational study - folkman, anne katrine; Hee Åker, Tone; Areskoug Josefsson , Kristina (Nordisk Tidsskrift for Helseforskning, 2023)
The purpose of this article is to add experience of co-production from a project in higher education, where the aim was the development of digital subjects in the field of sexual health. Observations of project meetings were analyzed with thematic analysis. Characteristics of the project such as management support emerged as there were expectations that participants were expected to work towards common goals in the project. The results showed that the co-production process was characterized by competence and information sharing between participants. The process was also characterized by positioning, in the sense that different professional prerequisites among the participants provided the basis for repeated discussions about the understanding and application of different theoretical perspectives and concepts. Specific professional interests and experiences influenced management and distribution of power in co-production both in the project manager groupmeetings and in the referencegroup meetings. Furthermore, the results highlight the need for open communication, shared goals and clear expectations for participation. The results indicate that co-production in the development of higher education can be demanding for both management and participants, but that at the same time there are opportunities to ensure evidence-based quality development based on the needs in the field of practice.
Keywords: Interprofessional digital courses; management; pedagogical innovation; co-production; sexual health